Pengaruh Kualitas Pelayanan Dan Citra Perusahaan Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Sebagai Variable Intervening Pada Bank KB Bukopin MT Haryono Jakarta - Nendy Yuliarrani; Dovina Navanti; Franciscus Dwikotjo Sri Sumantyo (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the influence of Service Quality and Company Image on Customer Loyalty through Customer Satisfaction as an Intervening Variable at Bank KB Bukopin MT Haryono Jakarta. This type of research is quantitative. The population in this study is unknown. The sampling technique uses Non-Probability Sampling using Purposive Sampling techniques. The sample in this study amounted to 112 respondents. Data collection technique by distributing questionnaires via Google Form. Hypothesis testing in this research uses Hypothesis testing in this research using Partial Least Squares (PLS) analysis. The research subjects were consumers of Bank KB Bukopin. The results of this research show that the service quality variable has a positive and significant effect on customer satisfaction at Bank KB Bukopin MT Haryono, company image has a positive and significant effect on customer satisfaction at Bank KB Bukopin MT Haryono, service quality has a positive and significant effect on customer loyalty at the Bank KB Bukopin MT Haryono, company image has a positive and significant effect on customer loyalty at Bank KB Bukopin MT Haryono, customer satisfaction has a positive and significant effect on customer loyalty at Bank KB Bukopin MT Haryono, service quality has a positive and significant effect on customer loyalty through customer satisfaction as intervening variables at Bank KB Bukopin MT Haryono and company image have a positive and significant effect on customer loyalty through customer satisfaction as an intervening variable at Bank KB Bukopin MT Haryono.